2008
DOI: 10.1038/mt.2008.116
|View full text |Cite
|
Sign up to set email alerts
|

AAV8-mediated Gene Transfer of Interleukin-4 to Endogenous β-Cells Prevents the Onset of Diabetes in NOD Mice

Abstract: We have demonstrated the ability to deliver and express genes specifically in beta-cells for at least 6 months, using a murine insulin promoter (mIP) in a double-stranded, self-complementary AAV vector (dsAAV8-mIP). In this study, we evaluated the effects of dsAAV8-mIP-mediated delivery of interleukin 4 (mIL-4) to endogenous beta-cells in nonobese diabetic (NOD) mice. In 4-week-old NOD mice, the extent of gene transfer and expression in endogenous beta-cells after ip delivery of dsAAV8-mIP-enhanced green fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…36,37 Our data indicate that AAV-mediated expression of GLP-1 in beta-cells following single intraperitoneal administration can mitigate the onset of diabetes in a model of type-1 diabetes. Targeted production of GLP-1 in beta-cells on its own, or coupled with a therapy designed to reduce autoimmune destruction, such as beta-cell expression of interleukin-4 as described by Rehman et al, 29 may represent a novel therapeutic strategy for type-1 diabetes.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Our data indicate that AAV-mediated expression of GLP-1 in beta-cells following single intraperitoneal administration can mitigate the onset of diabetes in a model of type-1 diabetes. Targeted production of GLP-1 in beta-cells on its own, or coupled with a therapy designed to reduce autoimmune destruction, such as beta-cell expression of interleukin-4 as described by Rehman et al, 29 may represent a novel therapeutic strategy for type-1 diabetes.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 99%
“…Furthermore, it has been shown that therapeutic genes can be delivered to beta-cells through intraperitoneal injection of AAV8. 29 Therefore, we sought to generate and deliver a GLP-1 transgene, expressed under the control of the insulin-II promoter, to beta-cells using this novel viral vector. To test the utility of this method of GLP-1 administration, we induced beta-cell apoptosis through low-dose streptozotocin (STZ) administration.…”
Section: Introductionmentioning
confidence: 99%
“…to young NOD mice. 116 Diabetes is prevented in NOD mice receiving dsAAV8-mIP-IL4, which correlates with reduced islet infiltration and an increase in FoxP3 + Treg in the periphery. Interestingly, no effect on β cell autoimmunity is detected in dsAAV8-mIP-IL10-treated NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the use of an insulin II promoter (IP) has proven to be highly effective for tightlyregulated and stable β cell-specific expression of rAAV encoded transgenes. 105,116 Evidence that T1D can be manipulated by targeting β cells in vivo is provided by a study in which dsAAV8 recombinants encoding IL-4 and IL-10 transgenes driven by a mouse IP (mIP) were administered i.p. to young NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…To bypass the need for systemic levels of immunomodulatory proteins to treat T1D, we have developed an approach for conferring long-term, local b-cell-specific expression by systemic gene transfer of self-complementary, double-stranded adeno-associated virus serotype 8 (dsAAV8) containing the murine preproinsulin-II promoter (MIP). 1 We have previously demonstrated that AAV gene transfer of interleukin-4 (IL-4) to endogenous b-cells in young, non-diabetic NOD mice prevented the onset of hyperglycemia in these mice and reduced the severity of insulitis. 1 However, although local expression of murine IL-4 in islets prevented islet destruction and blocked autoimmunity in NOD mice when administered before the onset of hyperglycemia, AAV-mediated gene transfer of IL-4 to b-cells of early-onset diabetic NOD mice was unable to reverse hyperglycemia (unpublished results).…”
Section: Introductionmentioning
confidence: 99%